Effectiveness of EDTA as the irrigation solution to remove smear layer in root canal - Kurniasri Amas Achiar; Endang Sukartini (Padjadjaran Journal of Dentistry, 2009)
One of the objectives of successful endodontic treatment is the hermetic obturation of the root canal system. To achieve this, the root canal filling must seal the canal space both apically and coronally to prevent the ingress of microorganisms or tissue fluids into the canal space. Apical leakage is reported a common reason for the clinical failure of endodontic therapy. Leakage through an obturated root canal is expected to take place at interfaces between sealer and dentin or sealer and gutta-percha, or through voids within the sealer. Hence, the sealing quality of root canal filling depends much on the sealing ability of the sealer. Therefore, anything that may influence the adaptation of the root filling to the canal wall is can determine the degree and the extent of leakage, and ultimately the prognosis of the endodontic therapy. In endodontic therapy, the smear layer formation results from root canal preparation and may influence the effective seal of the root canal system. The smear layer formation is mainly composed of inorganic components (dentin debris) and organic materials, such as pulp tissue remnant, bacteria, and blood cells. Removal of the smear layer from the root canal walls before the obturation can reduce the leakage of root canal sealer. To remove the smear layer use 10 ml 17% EDTA followed by 10 ml of 5.25% NaOCl as irrigating solution. This paper discribe about how the effectivity of EDTA as irigating solution to remove the smear layer especially in the apical root canal with many lateral canal to reduce the apical leakage.